Designing network security - Kaeo, Merike (Cisco Press, 2004)
Designing Network Security, Second Edition is a practical guide designed to help you understand the fundamentals of securing your corporate network infrastructure. In addition it provides a complete description of Cisco security products and useful implementation examples.